Influence of High Crystalline Amino Acid Inclusion on Poultry Diet Formulation and Pellet Quality - Kara M. Dunmire; Courtney N. Truelock; Jason Lee; Keith Haydon; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 3 broiler diets were pelleted to determine the effects of diet formulation on pellet quality. Dietary treatments consisted of corn and soybean meal (SBM)-based control, the control with crystalline Val, and the control with crystalline Val and Ile. As crystalline amino acids (AA) increased in the diets, corn concentrations increased as SBM and choice white grease (CWG) were removed to balance for nitrogen-corrected metabolizable energy (MEn). Diets contained 54.2, 56.4, and 57.5% corn; 39.1, 37.1, and 36.2% SBM; and 2.5, 2.1, and 1.9% CWG in the control, Val, and Val + Ile diets, respectively. Corn was ground to approximately 1,000 μm and used to mix 1,100 lb of feed per treatment. There were 3 replicates per treatment with time of processing as a blocking factor and treatment order randomized within each block. Diets were pelleted via steam conditioning (10 × 55 in., Wenger twin staff preconditioner, Model 150) using a pellet mill (CPM Model PM 1012-2 HD) equipped with a 3/16 × 1 ¼ in. pellet die. The target conditioning temperature was 185°F for 30 s at a 34 lb/min production rate. Pellet samples were collected and cooled in an experimental counterflow cooler for 15 min to determine percent fines, standard pellet durability index (PDI; ASABE S269.4, 2007), modified PDI (three 19-mm hex nuts) and Holmen NHP100 for 60 s. Hot pellet temperature decreased (P<0.01) in the control diet compared to Val and Val + Ile diets, which were 184.5, 185.1, and 185.088°F, respectively. Pellet mill kilowatts (kW) were 9.1, 8.9, and 10.3 for control, Val, and Val + Ile diets, respectively. Pellet mill kW increased (P<0.05) in pelleted Val + Ile diets compared to the control and Val diets. Percent fines decreased (P<0.01) and PDI increased (P<0.01) as crystalline AA increased and added fat decreased in the diet. For the control, Val and Val + Ile diets, PDIs were 66.5, 73.6, and 76.6% for the standard; 37.1, 46.9, and 52.8% for the modified; and 53.4, 67.8, and 73.7% for the Holmen NHP100 for 60 s methods, respectively. In conclusion, diets with increasing crystalline AA, Val, and Val + Ile, led to improved pellet quality, which can be explained by the 0.4% or 0.6% reduction in added fat with increasing crystalline AA and balancing for MEn in the diet.
Keywords: pellet quality; crystalline amino acids; fat; poultry